Base station placement for in-building mobile communication systems to yield high capacity and efficiency. - Butterworth, K.S (IEEE Transactions on communications)
A study is made of the problem of placing base stations to yield high capacity and efficiency in an in-building direct-sequence code-division multiple-access wireless communication system. A key requirement for solving this problem is a reliable but simple model of in-building propagation. A number of propagation models are considered as part of a system's performance analysis and are found to produce widely ranging levels of accuracy. Correlated shadowing is identified as being a `key'in-building propagation characteristic that has the potential to strongly influence the system's performance. Propagation models that included correlated shadowing are shown to produce the most accurate estimates of outage probability when there are a number of interferers facing a user. Base station deployment is shown to be a dominant factor influencing the levels of correlated shadowing, and consequently, base station deployment is shown to have major implications on the system's performance. The system's performance for a variety of base station deployment strategies has been determined. The results indicate that there is a tradeoff between system simplicity and performance